FRACTURE CRITERION OF THE THEORY OF CRITICAL DISTANCE FOR NOTCHES - LIU XiaoMei; BIAN YongMing; LIANG YongCheng; LI AnHu (Jixie qiangdu)
Whether the brittle fracture criterion of theory of critical distance is suitable for graphite plates with different shape notches was studied by means of analysis of finite element: including tensile specimens with U notches,blunted V-notch specimens of semi-circular bend,three-point bending specimens with single V-notch and compressed specimens of Brazilian disk.According to the theory of critical distance,the parameters of fracture toughness for two graphite materials were calculated by the calibrated characteristic distance and inherent strength and compared with the given values in the literature. The values of fracture loading for all notches under mode I were predicted and also compared with the experimental values. The theory of critical distance can not only predict the fracture loading and but also provide an engineering method to evaluate the fracture toughness by the fracture experiment of notched components. The theory of critical distance suitable for engineering just makes use of the numerical results,avoiding the complex analytical solutions of stress fields near the tip of notches,which is the best advantage.